Aportaciones del modelo interconductual al estudio de la lectura - Rueda Pineda, Elena; Guevara Benitez, Yolanda (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The inter-behavioral model has been proposed as an alternative way to approach psychological phenomena. In this study, we contextualized it by reviewing studies about reading generated from an operant conditioning model, and examining its limits for explaining complex linguistic behavior. We also applied theoretical proposals derived from the inter-behavioral model to the conceptualization of reading, retaking Ribes and López' (1985) taxonomy of behavior and Mares and Rueda's (1993) model of linguistic development. Finally, we reviewed applied contributions to the field, particularly those concerned with implementing programs that promote the development of more advanced levels of reading in beginners. We conclude by examining the model's implications for the field of education.